Low bone mineral density in children and adolescents with cancer - Hye Young Jin; Jun Ah Lee (Korean Society of Pediatric Endocrinology, 2020)
Maximizing accumulation of bone mass during childhood and adolescence is essential to attaining optimal peak bone mass. Childhood cancer survivors (CCS) have lower bone mineral density (BMD) than the general population. Chemotherapeutic agents including steroids and radiotherapy can affect BMD. Cancer itself, hormonal insufficiency, a poor nutritional state, and a deficit of physical activities during or after treatment also influence BMD in CCS, resulting in failure to achieve appropriate peak bone mass. Low BMD in childhood and adolescence can lead to osteoporosis in adult life and complications such as bone pain, bone deformity, and fractures. Thus, BMD in CCS should be monitored with appropriate intervention. Adequate intake of calcium and vitamin D and an increase in physical activity are recommended. Timely supplements of hormones are needed in some cases. Some publications have reported that bisphosphonate therapies using pamidronate or alendronate were well tolerated in CCS and helped increase BMD.